Growth Performances and Serum Biochemical Response of Broiler Chickens Fed on Diet Supplemented with Cyproheptadine as Substitute Growth Promoters (The International Journal for Scientific Research, 2023)
The aim of our study is to know the effect of adding cyproheptidine as a feed additive (growth promoter) to the broiler diet. Sixty birds (Ross breed) one day old were been grouped randomly into two groups: a treatment group and a control group, and the chicks were housing and feeding for 49 days (from 1/11 – 19/12/2022). and measure some serum biochemical parameter and growth performance.The result showed significantly affected (p
Keywords: Cyproheptidine; Broiler